The Effect of Fiscal Decentralization and Foreign Direct Investment on Regional Income Inequality: Economic Growth as A Mediating Variable - Triyono, T; Ariyani, Dwi; Sasongko, Noer (Universitas Muhammadiyah Surakarta, 2021)
This research aims to analyze the effect of fiscal decentralization and foreign direct investment (FDI) on regional income inequality and examine the role of economic growth in mediating the effect of independent variables on income inequality in Indonesia. The analytical tool used was path analysis (Path Analysis). The sample data were taken from 34 provinces in Indonesia in the period of 2015-2019. The results show (1) fiscal decentralization has a significant negative effect on economic growth in Indonesia in the period of 2015-2019. (2) FDI has a significant positive effect on economic growth. (3) Fiscal decentralization has a significant positive effect on income inequality. (4) FDI does not affect income inequality. (5) Economic growth has a significant positive effect on income inequality. (6) Economic growth cannot mediate the effect of fiscal decentralization on regional income inequality. (7) Economic growth can mediate the effect of FDI on regional income inequality.